Quality of life among patients with schizophrenia attending psychiatric clinic of Hospital Universiti Sains Malaysia - Wahid, Murniyati Abd (2010)
Quality of life assessments assist greatly in understanding the impact of illness and healthcare on patients' general well being, especially in the care of chronic mental patients. This intum helps to identify the specific interventions needed to improve their quality of life. Quality of life is assessed in broad range of different domains and is known to be associated with various factors. The aim of this study is to detennine the subjective quality of life and its association with socio demographic and clinical factors, and level of function among patients living with schizophrenia in community. A cross sectional study was conducted on 206 stable patients with schizophrenia living in community under psychiatric outpatient clinic, HUSM from 1st May to 31st October 2008. Systematic random sampling was applied and consented respondents were interviewed using Socio demographic and Clinical Characteristics Questionnaire. Brief version of Lehman's Quality of Life Interview - validated Malay Version was used to assess subjective quality of life, Calgary Depression Scale for Schizophrenia for depressive symptoms, Personal and Social Performance Scale for level of function and Positive and Negative Symptom Severity of Schizophrenia scale for psychiatric symptoms. Descriptive analysis, simple and multiple logistic regression were appropriately used for statistical analysis. Majority of the study participants were Malay (96.1% ), single ( 67.5% ), unemployed ( 62.6% ), educated until secondarary level (72.8%) with a family income of less than RM 500 per month ( 48.5% ). The mean age at first treatment is 24.6 (SD 8.9) years old. The median of both overall duration of illness and receiving treatment were 10 years (IQR 10). Majority were on monotherapy with atypical antipsychotics (57.3%), had mild psychiatric symptoms while a small number had depression (26.7%). Many had mild (45.6%) to moderate (53.9%) difficulties in functioning. Regarding the subjective quality of life, most participants were satisfied in every domain of quality of life even though concern was raised in social relations domain where nearly half perceived it as low. The significant associated factors for subjective quality of life were general psychopathology (OR=l.20, 95% CI=l.05,1.37) and depressive symptoms (OR=2.36, 95% CI=l.09, 5.07). Other socio demographic and clinical factors, and level of function were not significantly associated with subjective quality of life. The subjective quality of life among patients with schizophrenia living in community under follow-up at Hospital Universiti Sains Malaysia was perceived as satisfactory. The quality of life is strongly associated with the general psychopathology and severity of depressive symptoms.